Fertility preservation in Hong Kong Chinese society: awareness, knowledge and acceptance - Suet Ying YEUNG; Elaine Yee Lee Ng; Terence Tzu Hsi LAO; Tin Chiu Li; Jacqueline Pui Wah CHUNG (BMC, 2020)
Abstract Background Fertility preservation for both medical and non-medical reasons are gaining increasing attention world-wide. This study aimed to evaluate the awareness, knowledge and acceptance on fertility preservation in Hong Kong Chinese. Methods This was a cross-sectional study carried out between June 2016 to March 2017. A self-administered questionnaire was distributed by convenience sampling. Results Forty two percent of subjects returned the questionnaire (n = 296/697). Among them, only 54.3% were aware of any means of fertility preservation. Tertiary educated individuals are more aware than less educated individuals (73.6% versus 46.6%, p < 0.001). The most commonly known method is oocyte cryopreservation (94.3%). Most of the respondents (80%) were interested to know about fertility preservation, 84.1% considered fertility preservation counselling necessary and 83.3% would consider undergoing fertility preservation if a treatment has a high chance of causing infertility despite the possibility of delay in cancer treatment. Up to 93.9% agreed to set up a dedicated referral centre with government funding and 73.4% agreed that fertility preservation for medical indication should be provided as a government funded service. In terms of fertility preservation for non-medical reason, 65.5 and 70.4% agreed that fertility preservation should be offered to single men and women without partner respectively, while only 53.3 and 50% agreed that fertility preservation is acceptable for delay in childbearing for career development in female and male respectively. Conclusion There was a low awareness but positive attitude towards fertility preservation among Hong Kong Chinese. Acceptance towards medically indicated fertility preservation is high while a considerable number also accepts it for non-medical reasons. Educational campaigns are required to arouse awareness of fertility preservation to prevent individuals being deprived of the option due to lack of knowledge. Dedicated referral centre with established efficient patient referral pathways and financial support should be provided to improve the provision and uptake of fertility preservation service to enhance the reproductive potential and life options of women.